1989
DOI: 10.1152/jn.1989.62.5.1052
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular recording of identified neostriatal patch and matrix spiny cells in a slice preparation preserving cortical inputs

Abstract: 1. The morphology, electrical membrane properties, and corticostriatal excitatory postsynaptic potentials (EPSPs) of two groups of neostriatal projection cells, patch cells, and matrix spiny cells were compared in the rat by the use of an in vitro slice preparation that preserves inputs from medial agranular cortex. Spiny cells were stained intracellularly with biocytin and identified as belonging to the patch (striosomal) compartment or to the matrix by immunohistochemistry for the 28 kD calcium-binding prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
215
4

Year Published

1991
1991
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(265 citation statements)
references
References 0 publications
46
215
4
Order By: Relevance
“…The resting membrane potential of both matrix and patch cells has been reported to be approximately -7OmV (Kawaguchi et al 1989); however, long-lasting subthreshold depolarizations are commonly observed during which spikes are irregularly initiated (Wilson 1986). Thus the effective difference between resting and threshold potentials may be quite small.…”
Section: Discussionmentioning
confidence: 99%
“…The resting membrane potential of both matrix and patch cells has been reported to be approximately -7OmV (Kawaguchi et al 1989); however, long-lasting subthreshold depolarizations are commonly observed during which spikes are irregularly initiated (Wilson 1986). Thus the effective difference between resting and threshold potentials may be quite small.…”
Section: Discussionmentioning
confidence: 99%
“…These two groups of neurons are spatially compartmentalized within the striatum, with one group forming irregularly shaped patches within a surrounding matrix composed of neurons of the other class (Gerfen, 1984(Gerfen, , 1992Kawaguchi et al, 1989). Striatal neurons in each compartment receive distinct cortical afferents from specific cortical regions and laminas.…”
Section: Functional Differentiation Of Corticostriatal Pathwaysmentioning
confidence: 99%
“…Both Acb and caudate-putamen medium spiny neurons exhibit a strong inward rectification in the hyperpolarizing direction, a slow ramp-like depolarization visible just below spike threshold and a relative lack of frequency adaptation in spike trains (cf. Kita et al 1984Kita et al , 1985Kawaguchi et al 1989). Moreover, their time constants, input resistances as well as the shape and time 196 course of their postsynaptic responses are similar.…”
Section: Morphology and Membrane Properties Of Labeled Neuronsmentioning
confidence: 99%